Implementation of Cultural Arts Learning at SMA Negeri 3 Padang - Gevi Sonia, Citra; Hadi, Harisnal (Universitas Negeri Padang, 2023)
This study aims to determine and describe the implementation of cultural arts learning at SMA Negeri 3 Padang. The type of research used in this study is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and mobile phones. Data collection techniques include observation, interviews, literature studies and documentation. The steps in analyzing data are data collection, identifying data, classifying data, clarifying and inferring data. The results showed that the implementation of Cultural Arts learning at SMA Negeri 3 Padang had been carried out well, but there were several things in its implementation that were not in accordance with the teaching module so that the implementation of learning was still ineffective. In terms of the learning method used, the teacher has used a learning method that is in accordance with the material. However, when the teacher practiced the example of singing a popular Indonesian song, namely Anji's song entitled